Anaphylactoid Reaction to a Cyclooxygenase-2 Inhibitor in a Patient Who Had a Reaction to a Cyclooxygenase-1 Inhibitor - Schellenberg, R. Robert; Isserow, Saul H (The New England journal of medicine, 2001)
To the Editor: Recent studies 1 – 3 have suggested that cyclooxygenase-2 (COX-2) inhibitors can be safely used in patients with asthma who have documented intolerance to COX-1 inhibitors such as aspirin and nonsteroidal antiinflammatory drugs. On the basis of these observations, we chose to treat a subject who had had an adverse reaction to a nonsteroidal antiinflammatory drug with the COX-2 inhibitor rofecoxib (Vioxx) in a supervised hospital setting. A 63-year-old man with no history of asthma or allergic disease began treatment with diclofenac–misoprostol (Arthotec) in June 2001 for osteoarthritis. After one week of use, facial flushing and itching of the . . .